2010
DOI: 10.5251/abjna.2010.1.5.796.802
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration of metals in the head capsule and skeleton of Clarias gariepinus exposed to sublethal concentrations of soap and detergent effluents

Abstract: The sublethal toxicity of soap and detergent effluents from a soap and detergent industry were investigated on Clarias gariepinus using a renewable static bioassay. The bioconcentration of metals in the head capsule and skeleton were significantly different (P<0.05). The result revealed that the skeleton had the highest concentration of Iron at 38.0x10 . It can be deduced that the fish species has the tendency to bioaccumulate heavy metals from a polluted environment, which may lead to the impairment of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…This result supports research findings that ingestion of soap solution can cause multi organ damage leading to nervous system disorders, respiratory illness, cancer and even death [13,14]. Furthermore, the result is in line with reported pathological changes in animal and plant exposed to soap [15,16].…”
Section: Resultssupporting
confidence: 80%
“…This result supports research findings that ingestion of soap solution can cause multi organ damage leading to nervous system disorders, respiratory illness, cancer and even death [13,14]. Furthermore, the result is in line with reported pathological changes in animal and plant exposed to soap [15,16].…”
Section: Resultssupporting
confidence: 80%
“…Most of the human activities in Nigeria have resulted to the contamination of the environment. Substances such as crude oil, plastic waste, domestic waste, industrial effluent are major sources of pollutants in the environment (Ellis, 1989, Adewoye et al, 2005, Farombi et al, 2007, Ayandiran et al, 2009. Heavy metals such as lead, cadmium and mercury are not essential for man.…”
mentioning
confidence: 99%
“…Contamination of a river with heavy metals may cause effects on the ecological balance of the aquatic environment, and may narrow the diversity of aquatic organisms as the extent of contamination increases (Ayandiran et al 2009 ). Khayatzadeh and Abbasi ( 2010 ) reported that heavy metals in polluted reservoirs may also affect fi sh species at the population level.…”
Section: Effects Of Heavy Metals On Aquatic Lifementioning
confidence: 99%